The Role of Vowels and Consonants In English Language Learning - Lubis, Yani; Ramadhany, Cindy Alia; Widyana, Airen; Mahara, Elvida Futri; Sarahseti, Dian Fanny (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Numerous studies indicate that consonants are more highly valued for lexical interpretation than vowels because of the richer and more powerful distinctions they can make. Consonants appear to be the most important phoneme for differentiating between lexical items in most language systems. Cross-linguistically, consonants are more common than vowels. The title